Bimbingan Rohani Islam dalam Mengembangkan Spiritual bagi Korban Penyalahgunaan Napza - Leli Istikomah; Karomatun Nisak; Nur Azizah (Assertive: Islamic Counseling Journal, 2022)
The problem of drug abuse requires professional and serious handling because drug users can come from all walks of life and all ages. Treatment for victims of drug abuse (residents) can be through social rehabilitation with various programs and services to help residents recover; one of the programs is Islamic spiritual guidance services. This study aims to explain the implementation of spiritual guidance for spiritual development, which is carried out at the "Satria" Baturraden Center. The method used is a descriptive qualitative, with spiritual guidance officers as subjects and addiction counselors at the “Satria” Baturraden Center. Data collection was in the form of observations and interviews, which were then analyzed and supported by triangulation. The results are that Islamic spiritual guidance is essential to be given to residents undergoing drug rehabilitation. Implementing Islamic spiritual guidance can be done by providing motivational material and self-awareness associated with Islamic religious studies and supported by religious activities, such as: reading the Qur'an, praying five times a day, dhikr, and reading blessings, as well as activities other. Through Islamic spiritual guidance, residents can get many benefits that can be applied in daily worship activities while undergoing rehabilitation and after leaving the rehabilitation institution.